2012
DOI: 10.1161/circresaha.111.262519
|View full text |Cite
|
Sign up to set email alerts
|

Formin mDia1 Mediates Vascular Remodeling via Integration of Oxidative and Signal Transduction Pathways

Abstract: Rationale The mammalian Diaphanous-related formin, mDia1, governs microtubule and microfilament dynamics while functioning as an effector for Rho small GTP-binding proteins during key cellular processes such as adhesion, cytokinesis, cell polarity and morphogenesis. The cytoplasmic domain of the receptor for advanced glycation endproducts (RAGE) binds to the formin homology 1 (FH1) domain of mDia1; mDia1 is required for RAGE ligand-induced cellular migration in transformed cells. Objective As a key mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 55 publications
6
83
1
Order By: Relevance
“…Furthermore, we previously showed that the oxidative stress was a key mechanism by which RAGE mediated its effects. 25,34 This study supports the view that RAGE-mediated oxidative stress is important for the regulation of VSMC migration, thereby highlighting the link between RAGE and oxidative stress. Our results suggest a possible role for the SAA-RAGE interaction in the pathophysiology of uremic atherosclerosis.…”
supporting
confidence: 82%
“…Furthermore, we previously showed that the oxidative stress was a key mechanism by which RAGE mediated its effects. 25,34 This study supports the view that RAGE-mediated oxidative stress is important for the regulation of VSMC migration, thereby highlighting the link between RAGE and oxidative stress. Our results suggest a possible role for the SAA-RAGE interaction in the pathophysiology of uremic atherosclerosis.…”
supporting
confidence: 82%
“…The phosphorylation of PI3K is also essential for RAGE ligand-induced VSMC migration and proliferation. 24 In the present study, we found that specific signal inhibitors, PD98059 and U0126 for ERK1/2, SB203580 and SB202190 for P38-MAPK, and LY294002 and wortmannin for PI3K/Akt, markedly decreased AGEsinduced upregulation of K Ca 3.1 channel expression in rat VSMCs, indicating that activation of these cellular signaling pathways mediate the AGEs-induced increase of K Ca 3.1 channels. This is supported by previous reports, in which ERK induces an increase of proliferative gene expression, eg, the AP-1 family member c-fos, [25][26][27] and the increased production of c-fos leads to induction of K Ca 3.1 expression through AP-1 promoter elements.…”
Section: Discussionsupporting
confidence: 59%
“…We also expected that sRAGE would compete with cellsurface RAGE for h-IAPP binding, as it targets toxic LP intermediates and is a competitive inhibitor of ligand binding to cell membrane-bound RAGE. To test this, we used INS-1 β cells and primary murine aortic smooth muscle cells (SMCs) as model systems (50,52). We prepared h-IAPP LP intermediates, a 1:1 molar mixture of h-IAPP/sRAGE, and multiple controls including sRAGE, r-IAPP, and buffer-only solutions.…”
Section: Rage Significantly Contributes To H-iapp-mediated Cellular Pmentioning
confidence: 99%